Conventional realism and political inquiry : channeling Wittgenstein - Gunnell, John G. (Chicago : The University of Chicago Press, 2020)
"This book is an exploration of the relationship between philosophy and political inquiry. John G. Gunnell is seeking to explain certain dimensions of how philosophy has influenced political science and political theory but also how these latter fields have understood and deployed philosophy. When social scientists and social theorists turn to the work of philosophers for intellectual authority what they extract is often selective and in the service of some prior agenda. The philosophers whose work he discusses have all in various degrees been objects of the conversation of political theory, but close acquaintance with that work is often limited and derivative. Gunnell's goal is to initiate a more genuine "conversation" with certain philosophers and political theorists"--
Representational Philosophy and Conventional Realism -- Mentalism and the Problem of Concepts -- The Realistic Imagination in Political Inquiry: The Case of International Relations -- The Challenge to Representational Philosophy: Wittgenstein, Ryle, and Austin -- Contemporary Anti-representationalism: Sellars, Davidson, Putnam, McDowell, and Dennett -- Presentation and Representation in Social Inquiry -- Conventional Realism -- The Quest for the Real and the Fear of Relativism.
Includes bibliographical references and index.
Binding: Includes original dust-jacket.
Keywords: Wittgenstein, Ludwig, -- 1889-1951.; Political science -- Philosophy